MET Receptor Tyrosine Kinase Regulates Lifespan Ultrasonic Vocalization and Vagal Motor Neuron Development - Kamitakahara, Anna K.; Ali Marandi Ghoddousi, Ramin; Lanjewar, Alexandra L.; Magalong, Valerie M.; Wu, Hsiao-Huei; Levitt, Pat (Frontiers in Neuroscience, 2021)
The intrinsic muscles of the larynx are innervated by the vagal motor nucleus ambiguus (nAmb), which provides direct motor control over vocal production in humans and rodents. Here, we demonstrate in mice using the Phox2bCre line, that conditional embryonic deletion of the gene encoding the MET receptor tyrosine kinase (MET) in the developing brainstem (cKO) results in highly penetrant, severe deficits in ultrasonic vocalization in early postnatal life. Major deficits and abnormal vocalization patterns persist into adulthood in more than 70% of mice, with the remaining recovering the ability to vocalize, reflecting heterogeneity in circuit restitution. We show that underlying the functional deficits, conditional deletion of Met results in a loss of approximately one-third of MET+ nAmb motor neurons, which begins as early as embryonic day 14.5. The loss of motor neurons is specific to the nAmb, as other brainstem motor and sensory nuclei are unaffected. In the recurrent laryngeal nerve, through which nAmb motor neurons project to innervate the larynx, there is a one-third loss of axons in cKO mice. Together, the data reveal a novel, heterogenous MET-dependence, for which MET differentially affects survival of a subset of nAmb motor neurons necessary for lifespan ultrasonic vocal capacity.